Educational Big Data and Its Functions - Duykuluoğlu, Ayhan; Dumitrascu, Alina; Martinez, Marian Navarro; Simarro, Juan Francisco Blesa (Technium Education and Humanities, 2023)
An understanding towards the economic value of data led the organizations to collect more data and this paved the way for the term “big data” to arise. Today especially the companies that operate in e-trading add to the importance of “big data” by transforming data into financial gain. The inner characteristic of data as a source which does not run our when spent places it in a special location among all organizational assets. Along with the pandemic, educational activities were transferred to the digital platforms and this increased the importance of big data in education systems. The digital platforms contributed to the collection of more data about students’ academic performance, their learning styles, preferences and tendencies. This kind of data can be utilized for different purposes such as improving digital learning platforms, individualization of learning processes, developing teaching processes based on data and providing real time flowing data about academic performances of students. Learning is an individual process and data about individual needs, preferences, styles and tendencies can help develop individualized learning and teaching ecosystems at schools and school areas. This study aims at developing a framework for the functions of big data in the field of education.